Perancangan Sistem Informasi Parkir Pada Klinik XYZ - Kusumawati, Arie; Setya, M. Donny (I-STATEMENT: Information System and Technology Management, 2016)
Information and communication technology (ICT) has evolved. The amount of benefits making ICT as needs as well as the requirements for the organization in running the business. ClinicXYZ is currently experiencing very rapid progress. However, clinical progress brings its own problems. One is the increasing number of vehicles and the growing density of activity in the limited parking lot. XYZ Clinic parking lot currently managed manually, so there are still many problems that arise. Therefore, there are needs for a new system that could be the solution of the existing problems. Parking Information System Clinic XYZ is built using the Java programming language and MySQL. The system can handle the process of managing the parking attendant, parking transactions both in and out of vehicles as well as printing ticket and searching of old transaction data.